Supportive care in advanced chronic kidney disease: Comprehensive conservative care - Belino,C (2018)
Incident and prevalent patients on dialysis are progressively older, with high comorbidity burden and functional dependency. Many could have benefited from a conservative approach, since considerations of symptoms, autonomy, quality of life and hospital-free days are sometimes more important for patients and families than survival. As result, nephrologists around the world are facing challenges to determine which treatment best fits their patients. Comprehensive conservative care in chronic kidney disease care has been recently defined as a holistic, multidisciplinary and patient-centered approach for care of patients with stage 5 CKD. It does not include dialysis, and a shared-decision-making process and advanced care planning are central pillars, providing a way to meet patient and families goals. This review will focus on comprehensive conservative care in CKD in order to provide a communication framework for decision-making process as a guide for nephrologists and other health care professionals.